The Performance of Electricity Producing of Dual Chamber Microbial Fuel Cells (MFCs) Using Wastewater of Tempe Industries - Luthfiah, Yayah; Artsanti, Pedy (Proceeding International Conference on Science and Engineering, 2017)
The performance of electricity producing of Dual Chamber Microbial Fuel Cells (MFCs) using wastewater of tempe industries without glucose addition (as control substrate) and with (2% and 4%) glucose addition was observed. The anode chamber contained a waste substrate and a cathode chamber contained a 0.1 M Potassium Permanganate electrolyte solution. The salt bridge was required to stabilize the charge between the cathode and anode chambers, and the electrodes attached to the anode and cathode chambers as the electron catcher. Voltages and currents were measured using multimeter. Optical Density measured at 486 nm wavelengths was performed to estimate bacterial growth activity. All of the cells were observed for 72 hours of running time. The results of Optical Density curves showed an increasing trend of absorbance during 72 hours of running time. These were in agreement with the resulting power density, which tended to increase until the 48th hour and then relatively stable especially for the substrate with 4% glucose addition. These MFCs system could also reduce COD by 1.52%, 9.76%, and 9.64% on control substrate, 2% glucose addition substrate, and 4% glucose addition substrate, respectively.